IMPLEMENTASI KEBIJAKAN PENGELOLAAN BARANG MILIK NEGARA BERUPA TANAH PADA DIREKTORAT JENDERAL PENDIDIKAN TINGGI, RISET DAN TEKNOLOGI KEMENDIKBUDRISTEK - Siregar, Mario Bungaran; Daraba, Dahyar; Ruhana, Faria (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The Directorate General of Higher Education, Research, and Technology (Ditjen Diktiristek), which is one of the main units in the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek), is responsible for the use and management of state-owned assets in the form of land, in line with its duties and functions in providing higher education services. This research aims to describe and analyze the factors that hinder the implementation of policies related to the management of state-owned land assets within Ditjen Diktiristek Kemendikbudristek, particularly in higher education institutions (PTNs). The study employs a qualitative research method with a descriptive approach, using the four-dimensional policy implementation analysis framework proposed by Edwards III (1984), which includes communication, resources, disposition, and bureaucratic structure. Data collection for this research involved observations, interviews, and documentation. In analyzing the data collected, the researcher used models including data reduction, data presentation, and conclusion drawing or verification. Data for the study were obtained from fourteen informants, including the Director General of Diktiristek and his staff, as well as leaders of PTNs and relevant officials. Referring to the four dimensions proposed by Edward III, the communication dimension highlights the lack of information flow from the Directorate General of Higher Education, Research, and Technology (Ditjen Diktiristek) to public universities (PTN). PTNs do not receive sufficient information on how to implement regulations related to state-owned land assets (BMN). The resource dimension indicates that the quantity of human resources at both Ditjen Diktiristek and PTNs in managing state-owned land assets is inadequate, and the budget conditions have not yet reached the ideal amount. The disposition dimension shows that the response of the implementers at PTNs tends to be slow during the execution of policies related to managing state-owned land assets. As for the bureaucratic structure dimension, it is evident that there is no specific SOP outlining the handling of problematic state-owned land assets, and internal fragmentation occurs within PTNs, where the responsibility for managing these assets is often spread across various units or faculties